Classification and Lexico-Semantic Feature of Cliched Units - Maktuba Sattorova; Elkin Denis Yurievich (Periodica Journal, 2023)
This study describes the symbolic meanings of numbers in phraseological units. The article presents the varieties of functions of number words at present. Relations between the terms number and word are studied.
Keywords: lexicosemantic features; number; numerical phraseological unit